2021
DOI: 10.3390/admsci11040117
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility through SDGs: Preliminary Results from a Pilot Study in Italian Universities

Abstract: Background: In the broad scientific debate on the integration of corporate social responsibility (CSR) in the strategic planning of universities and on the use of monitoring the results of the strategy of the indicators relating to the pursuit of sustainable development goals (SDGs), there is a lack of studies demonstrating the effective degree of institutionalization of CSR in universities. Methods: This analysis constitutes a pilot study relating to the Italian university context. The study was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…In a study, Castillo-Villar (2020) conducted a cross-sector partnership analysis in the context of the 2030 Agenda, identifying those CSR determinants that could contribute to the realization of SDG18 Partnership for Goals in universities. In addition to Castillo-Villar (2020), Costa et al (2021) also placed the realization of goals and the study of the context of CSR in a university setting. In addition, the literature gives an example of a diagnostic tool to aid the design of better interventions for achieving the SDGs in the case of multinational companies through using a responsibility matrix model.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, Castillo-Villar (2020) conducted a cross-sector partnership analysis in the context of the 2030 Agenda, identifying those CSR determinants that could contribute to the realization of SDG18 Partnership for Goals in universities. In addition to Castillo-Villar (2020), Costa et al (2021) also placed the realization of goals and the study of the context of CSR in a university setting. In addition, the literature gives an example of a diagnostic tool to aid the design of better interventions for achieving the SDGs in the case of multinational companies through using a responsibility matrix model.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, the literature gives an example of a diagnostic tool to aid the design of better interventions for achieving the SDGs in the case of multinational companies through using a responsibility matrix model. Some articles also address the field of business ethics and brand loyalty in search of the mediating role of corporate social responsibility and perceived green marketing through the contribution of the SDGs (Castillo-Villar, 2020; Costa et al, 2021;Amoako et al, 2021). Some articles put the emphasis on the relation between perceived SDG regarding economic, social or environmental progress over the past 2 years of the COVID-19 pandemic and specifically focus on customers' perceptions (Lorgnier et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The third paper is "Corporate Social Responsibility through SDGs: Preliminary Results from a Pilot Study in Italian Universities" by Costa et al (2021). This research focuses on the three-year strategic performance plans (2020-2022) of Italian universities to investigate the effective degree of institutionalization of CSR in universities.…”
Section: The Collection Of Articlesmentioning
confidence: 99%
“…Various authors evaluated the presence of sustainability in universities in Italy. Costa et al (2021) evaluated 67 universities in this IJSHE 24,4 country to verify the presence of SDGs in their official documents and found that, out of 67 HEIs, only 11 (16%) had institutionalized these objectives. According to the authors, "the pilot study highlight that CSR practices and challenges of SD are not systematically addressed in the strategic planning of Italian universities" (p. 11).…”
Section: Higher Education Institutionsmentioning
confidence: 99%
“…In this regard, SD can be viewed as an innovation in the university system because it involves transformative learning, which implies a great challenge of facing the complexity of implementing systemic thinking and the barrier of disciplinary division (Ferrer-Balas et al , 2009). In recent decades, university institutions have been called on to rethink their models, adopting a more responsive position in relation to society’s needs and assuming the role of change agents (Costa et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%